Dampak Penyerapan Anggaran Terhadap Kinerja Instansi Pemerintah (Studi Kasus di Provinsi Jambi) - Arniwita Arniwita; Agus Santoso; Endah Tri Kurniasih; Ahmad Soleh (Ekonomis: Journal of Economics and Business, 2019)
The regional budget is an important instrument in the administration of public services, so that it can provide benefits to the welfare of the community. However, in its implementation there are still many that have not been fulfilled as a result of suboptimal absorption of the budget that impacts government performance. Therefore, the problem of delays in budget absorption and low levels of budget absorption must be addressed immediately. Based on this problem, this research was conducted. The purpose of this study is to analyze the tendency of budget absorption, analyze the factors that influence the absorption of the SKPD expenditure budget in the Jambi Provincial Government, analyze the influence of SKPD expenditure absorption on agency performance and look for appropriate policy strategies in efforts to improve financial and service performance Jambi Provincial Government. The results of the analysis show that 1) when viewed from the total expenditure, all SKPD of the Provincial Government of Jambi tends to experience delays in budget absorption, and when viewed per type of expenditure, 82.61% SKPD tends to experience a delay in absorption of the personnel expenditure budget, all SKPDs tend to experience delays budget absorption of goods and services expenditure, and 43.90% SKPD tend to experience delays in capital expenditure budget absorption; 2) budget planning and budget execution are factors that significantly influence the uptake of the budget while human resource capacity (HR) has no significant effect; 3) budget absorption has a positive and significant effect on agency performance.